Designing A System Dynamics Pattern of Marketing in Sport Tourism Destinations; A Qualitative Research - Abbas Naghizadeh-Baghi; Majid Javid; Mohammad Heidari; Samad Goodarzi (Research in Sport Management and Marketing)
Purpose: Destination marketing is now as a pillar of the growth and sustainability of tourism destinations ensure of growth and economics development of destinations in the competitive in an increasingly globalized and competitive market for tourists. The purpose of present study was to designing pattern for marketing of sport tourism destinations in Ardabil province. Methods: This study was an applied research on. Thus, this research was conducted using qualitative approach. Statistical population of this study consisted of sport management experts, tourism and economy experts, managers of cultural heritage & tourism department, managers of Sport & youth department, provincial government managers, municipality managers, parliament members & tourism agencies managers of Ardabil province. Mixed of some theoretical sampling methods were utilized to select the samples of this study, unstructured qualitative interviews were conducted to collect data in our study. Theoretical saturation was obtained following 21 interviews. data analysis were conducted systematically by using thematic analysis method in Nvivo 12 Plus software.Results: 61 codes were identified after analyzing data which were classified in 7 main classes (Informing and advertising, Tourism packages, Destination brand, Motivation and encouragement, Destination Image and Destination Endorsements) based on their importance. Finally, the Pattern of the dynamic system of marketing sport tourism destinations was drawn with Vensim PLE.Conclusion: The results of present study provide the politicians and planners of this province with adequate approaches to approaches to accelerate the development of tourism destinations economically in Ardabil Province.